Effectiveness of Behavioral Attitude Assessment Instruments in Structural Leadership Training - Eris Yustiono (Innovation Business Management and Accounting Journal, 2025)
This study examines the effectiveness of behavioral attitude assessment instruments used in structural leadership training programs by analyzing how instrument- and assessor-related conditions shape their validity, reliability, objectivity, and practicality. Employing a quantitative approach enriched with qualitative feedback, data were collected from 41 facilitators (widyaiswara in Indonesian terminology) from the PKASN Training Center and other government training institutions. The findings indicate that while the instrument is practical and easy to apply, its effectiveness is constrained by weaknesses in validity, reliability, and objectivity. These limitations are associated with inconsistent interpretation of indicators, the presence of subjective bias, and the absence of standardized observation guidelines, all of which reduce inter-rater reliability and behavioral accuracy. The study highlights that instrument effectiveness is not solely determined by its design but also by how it is interpreted and implemented in practice. The findings underscore the need for evidence-based evaluation instruments that promote fairness, accuracy, and accountability in leadership development programs and support the development of more objective and behaviorally grounded assessment systems in government training institutions.